Pretreatment of forestry residue via torrefaction process - Ayuni, Mohamad Ali (2015)
The use of biomass to produce energy is becoming more and more frequent as it helps to achieve a sustainable environmental scenario. However, the exploitation of this fuel source does have drawbacks that need to be solved. In this work, the torrefaction of forestry residues was studied in order to improve its properties as an alternative fuel for renewable energy sources. The torrefaction process was conducted at 230 °C, 270 °C and 300 °C with a residence time of 30 minutes and in the absence of oxygen. From the torrefaction experiment, characteristics such as heating value, mass and energy yield were determined. From the results obtained, the heating values of torrefied biomass increased when the temperature were increased in the range of 18 to 21 MJ/kg at various torrefaction conditions. The overall mass yield of torrefied biomass was decreased when temperature was increased from 230 to 300 °C and in the range of 84 - 93%. The energy yield for torrefied biomass increased when the temperature was increased in the range of 85 to 99%. The torrefied biomass can be pelletized as an alternative to replace the usage of charcoal in commercial and industrial sector.